ARID1A deficiency attenuates the response to EGFR-TKI treatment in lung adenocarcinoma - Yang, Fangfang; Hou, Helei; Wang, Guanqun; Fu, Guangming; Huo, Xingfa; Duan, Xueqin; Zhou, Na; Zhang, Xiaochun (Frontiers in Pharmacology, 2025)
BackgroundConcurrent genetic alterations (e.g., TP53 comutations) significantly impair EGFR-TKI responsiveness and survival outcomes in EGFR-mutant lung adenocarcinoma (LUAD). AT-rich interactive domain 1A (ARID1A), which is a key subunit of SWI/SNF complexes, demonstrates critical regulatory functions as a tumour suppressor gene in cancer. The aim of this study is to determine the role of ARID1A deficiency in the therapeutic efficacy of EGFR-TKIs in LUAD.MethodsWe identified the ARID1A mutation as a potential prognostic marker in EGFR-mutant LUAD by analysing data from cBioPortal. The expression of ARID1A was detected via immunohistochemical staining. A lentivirus was employed to construct the ARID1A knockdown model in PC9 cell. We further analyzed the biological roles of ARID1A knockdown through CCK8, flow cytometry analysis and transwell assay.ResultsThe ARID1A mutation was associated with poor OS in EGFR-mutant LUAD patients, and the prognostic influence was greater than that of concurrent EGFR mutations with TP53, KRAS, CDKN2A, PIK3CA, RB1 or PTEN. By analysing the clinical data of our centre, we revealed that patients with loss of ARID1A expression demonstrated poorer median progression-free survival (mPFS, 10.3 versus 30 months, P = 0.005) when they received EGFR-TKIs as the first-line treatment after postoperative progression (cohort A). A shorter median disease-free survival (mDFS, 29 versus NA months, P = 0.003) was also observed in the ARID1A low-expression cohort than in the ARID1A high-expression group in patients receiving postoperative adjuvant EGFR-TKI treatments (cohort B). We also found that ARID1A deficiency attenuated the efficacy of osimertinib by activating the EGFR/AKT/mTOR signalling axis in PC9 cell.ConclusionARID1A deficiency may be an independent prognostic factor and attenuates the response to EGFR-TKIs in patients with EGFR-mutant LUAD. In addition, loss of ARID1A expression confers resistance to EGFR-TKI by activating the EGFR/AKT/mTOR signalling axis.